The Virtues of Self-Regulated Learning Strategy in Writing: A Scoping Review - Candradewi Wahyu Anggraeni; Januarius Mujiyanto; Katharina Rustipa; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2022)
Self-Regulated Learning (SRL) strategy is an autonomous learning strategy in which students have an essential role in regulating their learning. Self- Regulated Learning (SRL) strategy consists of three essential phases (forethought phase, performance phase, and self-reflection phase). This study aims to summarize and disseminate research findings on the virtues of Self- Regulated Learning (SRL) strategy in writing. This article presents a scoping review of 10 (ten) articles from 2018 to 2022 focused on Self- Regulated Learning (SRL) strategy in writing. A scoping review is one of the literature review methods that aims to give in-depth resources that depend on review purposes. Dealing with the steps of a scoping review, Arksey and O'Malley (2005) highlight five important stages in conducting a scoping review; identifying the research question, identifying relevant studies; study selection; charting the data; and collating, summarizing, and reporting. A noteworthy finding of this scoping review deals with the advantages of Self- Regulated Learning (SRL) in writing which cover SRL enhances academic accomplishment, fosters writing abilities, plays an important role in the writing process, and assists students in writing better.